Tinjauan Kriminologis Pada Pelaku Tindak Pidana Eksploitasi Seksual Terhadap Anak Dibawah Umur - Nuke Rouffyanti Abdillah; Oci Senjaya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Indonesia is part of a legal state, this is stated in Article 1 Paragraph 3 of the 1945 Constitution of the Unitary State of the Republic of Indonesia. Children are state assets which are also legal subjects protected by law. The aspect of state responsibility is present through the establishment of the Child Protection Act. However, with this legal product, it is still lacking in handling cases of children, one of which is the crime of sexual exploitation of minors. This research uses a normative juridical approach. Normative jurisprudence is the study of the legal basis, legal system, level of legal agreement, and comparative law. This normative juridical is an attempt to take an inventory of positive law. In this approach, prescriptive rules are used to explore legal issues of compliance with social life.